Alcohol outlet density and related use in an urban Black population in Philadelphia public housing communities. (January 2015) - Cederbaum, Julie A.; Petering, Robin; Katherine Hutchinson, M.; He, Amy S.; Wilson, John P.; Jemmott III, John B.; Sweet Jemmott, Loretta
Abstract: Adolescent alcohol use behaviors are influenced by familial patterns and neighborhood factors. This work explored the influence of individual, family, and environment on alcohol use. Baseline data from a randomized controlled trial with Black mothers son dyads ( n =382) were paired with census tract and alcohol control board data. Among mothers, younger age, along with neighborhood factors of alcohol outlet density, race, and education were significantly associated with use. Among sons, older age and alcohol outlet density in the neighborhood predicted use. Findings highlight neighborhood influence, beyond family qualities, as a significant determinant of disadvantaged Black mothers' alcohol use. Implications for public health policy are discussed.